Advances in the Pathogenesis, Diagnosis and Treatment of Bow Hunter's Syndrome: A Comprehensive Review of the Literature - Duan, Guangxin (Interv Neurol, 2016)
Bow hunter's syndrome (BHS), also known as rotational vertebral artery (VA) occlusion syndrome, is a rare yet treatable type of symptomatic vertebrobasilar insufficiency resulting from mechanical occlusion or stenosis of the VA during head and neck rotation or extension. The symptoms of BHS range from transient vertigo to posterior circulation stroke. The underlying pathology is dynamic stenosis or compression of the VA by abnormal bony structures with neck rotation or extension in many cases, such as osteophyte, disc herniation, cervical spondylosis, tendinous bands or tumors. Imaging approaches, such as Doppler sonography, computed tomography and angiography, as well as magnetic resonance imaging and angiography, are widely used in the diagnosis and evaluation of this syndrome. Digital subtraction angiography with head rotation remains the gold standard diagnostic method. Conservative management, surgery and endovascular procedures are the three major treatment methods for BHS, whereas some symptomatic patients may need operative treatment including surgery and endovascular procedures when conservative management is not adequate.